Identification of the C-terminal region in Amelogenesis Imperfecta causative protein WDR72 required for Golgi localization - Dina Husein; Ahmed Alamoudi; Yoshio Ohyama; Hanna Mochida; Brigitte Ritter; Yoshiyuki Mochida (Scientific Reports, 2022)
Abstract Amelogenesis Imperfecta (AI) represents a group of hereditary conditions that manifest tooth enamel defects. Several causative mutations in the WDR72 gene have been identified and patients with WDR72 mutations have brown (or orange-brown) discolored enamel, rough enamel surface, early loss of enamel after tooth eruption, and severe attrition. Although the molecular function of WDR72 is not yet fully understood, a recent study suggested that WDR72 could be a facilitator of endocytic vesicle trafficking, which appears inconsistent with the previously reported cytoplasmic localization of WDR72. Therefore, the aims of our study were to investigate the tissues and cell lines in which WDR72 was expressed and to further determine the sub-cellular localization of WDR72. The expression of Wdr72 gene was investigated in mouse tissues and cell lines. Endogenous WDR72 protein was detected in the membranous fraction of ameloblast cell lines in addition to the cytosolic fraction. Sub-cellular localization studies supported our fractionation data, showing WDR72 at the Golgi apparatus, and to a lesser extent, in the cytoplasmic area. In contrast, a WDR72 AI mutant form that lacks its C-terminal region was exclusively detected in the cytoplasm. In addition, our studies identified a putative prenylation/CAAX motif within the last four amino acids of human WDR72 and generated a WDR72 variant, called CS mutant, in which the putative motif was ablated by a point mutation. Interestingly, mutation of the putative CAAX motif impaired WDR72 recruitment to the Golgi. Cell fractionation assays confirmed subcellular distribution of wild-type WDR72 in both cytosolic and membranous fractions, while the WDR72 AI mutant and CS mutant forms were predominantly detected in the cytosolic fraction. Our studies provide new insights into the subcellular localization of WDR72 and demonstrate a critical role for the C-terminal CAAX motif in regulating WDR72 recruitment to the Golgi. In accordance with structural modelling studies that classified WDR72 as a potential vesicle transport protein, our findings suggest a role for WDR72 in vesicular Golgi transport that may be key to understanding the underlying cause of AI.